P061 CYCLOSPORINE INDUCED KAPOSI SARCOMA IN AN IBD PATIENT: A DOWNWARD SPINDLE. (7th February 2019) - Chandler, Matthew; Stachura, Anna; Clarke, Lindsay M; Theisen, Brian; Borum, Marie L
Abstract: Background: Kaposi Sarcoma is an angioproliferative neoplasm found to be associated with human herpesvirus-8 (HHV8). Although this virus plays a role in the pathogenesis of the disease, in individuals who are human immunodeficiency virus (HIV) negative, it is exceedingly rare. Still, there have been documented cases of individuals developing gastrointestinal Kaposi sarcoma in the setting of immunosuppression, specifically solid organ transplant patients, and less frequently inflammatory bowel disease (IBD). Case Presentation: We report a 24-year-old HIV-negative man with a history of ulcerative colitis (UC), psoriasis, atopic dermatitis, and alopecia aereata who was referred to the gastroenterology clinic after experiencing 12 episodes of watery non-bloody diarrhea per day and 20 lb. weight loss over the duration of one-month. Onset of watery diarrhea coincided with starting antibiotics (amoxicillin) for periodontal abscess. Patient reported that since his UC had been well-controlled for several years on cyclosporine prior to his presentation, he attributed the diarrhea and weight loss to antibiotic use. He was initially diagnosed with UC at age 15 and had previously been treated with multiple agents including adalimumab and intermittent prednisone without optimal response. Evaluation showed that he was positive for enteropathic E. coli and norovirus which was thought to be contributing to the diarrhea; he was negative for Giardia, Clostridium difficile, and stool cultures. Given his ongoing symptoms and history of UC, colonoscopy was performed which demonstrated multiple hemorrhagic nodules throughout the colon and terminal ileum. Biopsy results showed vasoformative spindle cell lesions compatible with Kaposi sarcoma that was HHV-8 positive and CMV negative in the terminal ileum and colon. CT chest/abdomen/pelvis demonstrated diffuse lymphadenopathy. He underwent right axillary lymph node biopsy which was consistent with Kaposi sarcoma. His cyclosporine and Truvada were discontinued. Oncology was consulted for further management. Discussion: Since 1966, there have been only 16 cases of patients documented with IBD developing Kaposi sarcoma secondary to immunosuppressive therapy. Frequently, these patients were on prednisone or biologics with only two patients receiving cyclosporine for a brief period during the course of their therapy. Iatrogenic Kaposi sarcoma has been documented among transplant patients. We report a rare case of an individual with ulcerative colitis developing iatrogenic Kaposi sarcoma in the setting of long-term cyclosporine therapy. (A & B) H&E stained tissue sections of the colon biopsies demonstrates a vasoformative lesion composed of spindle cells with many small, poorly formed, slit-like vascular spaces involving the lamina propria and submucosa. Immunohistochemical stains demonstrate that this lesion is positive for endothelial markers CD31 (C) and CD34 (not pictured) as well as for Human Hepesvirus 8 (HHV-8) (D).